A Geografia dos primeiros povos da terra: reflexões a partir do Atlas Historique Mondial, de Christian Grataloup - Confins (Confins)
The origin of human groups on earth, as well as their movement, is one of the many themes addressed in Christian Grataloup's World Historical Atlas. In this publication we explore some of these maps and their commentaries, instigating a geographical reading of the cartographic material available on a public acess platform.